Pengaruh Inovasi dan Kualitas Produk Kopi Rempah Bapak Ali di Sumberanyar Mlandingan terhadap Kepuasan Konsumen - Arini Hidayati; Lusy Endang Sri D; Agusti Agusti (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The coffee industry, particularly in Indonesia, is experiencing rapid growth, driven by increasing public interest in local products with unique flavors and distinctive tastes. The purpose of this study is to examine the interaction between innovation and product quality in influencing consumer satisfaction with spiced coffee products. With the rise of local coffee brands, particularly spiced coffee, understanding consumer satisfaction becomes crucial for maintaining competitive advantage. This study adopts a qualitative approach to explore consumer experiences, perceptions, and perspectives regarding the innovation and quality of Mr. Ali's spiced coffee products. The qualitative method allows for an in-depth exploration of social and cultural phenomena, providing valuable insights into how consumers perceive innovation and product quality. Through in-depth interviews and participant observations, the research reveals that consumers value the integration of unique flavors and high-quality ingredients in their coffee experience. The study concludes that there is a mutually reinforcing relationship between product innovation, product quality, and consumer satisfaction. Mr. Ali's spiced coffee products have successfully met customer expectations by introducing relevant innovations, using high-quality raw materials, and offering responsive and personalized customer service. These factors collectively contribute to enhanced consumer satisfaction, reinforcing the importance of continuous innovation in the coffee industry.